A cost-utility analysis of SIR-Spheres Y-90 resin microspheres versus best supportive care in the treatment of unresectable metastatic colorectal cancer refractory to chemotherapy in the UK. (1st December 2020) - Brennan, V. K.; Colaone, F.; Shergill, S.; Pollock, R. F.
Abstract: Background: Limited treatment options are available in chemotherapy-refractory or -intolerant metastatic colorectal cancer (mCRC). The objective of the present analysis was to evaluate the cost-utility of SIR-Spheres Y-90 resin microspheres relative to best supportive care (BSC) in the treatment of chemotherapy refractory mCRC from the perspective of the UK national healthcare payer. Methods: A cost-utility model was developed in Microsoft Excel to simulate transitions from progression-free survival to post-progression survival and death in patients with mCRC. Unit costs were captured in 2019 pounds sterling (GBP) based on the literature, formulary listings, and National Health Service (NHS) England reference costs. Future costs and effects were discounted at 3.5% per annum . A series of one-way sensitivity analyses, and probabilistic sensitivity analysis (PSA) were conducted. Results: The base case analysis showed that SIR-Spheres Y-90 resin microspheres would result in an increase in discounted quality-adjusted life years gained from 0.69 quality-adjusted life years (QALYs) to 1.50 QALYs, with an associated increase in cost from GBP 15, 268 to GBP 34, 168 yielding an incremental cost-utility ratio of GBP 23, 435 per QALY. PSA showed that there would be a 56% likelihood that SIR-Spheres Y-90 resin microspheres would be cost-effective relative to BSC at a willingness-to-pay threshold of GBP 30, 000 per QALY gained. Conclusions: This cost-utility analysis showed that, relative to BSC, SIR-Spheres Y-90 resin microspheres would be a cost-effective treatment option for patients with mCRC in the UK setting from the national healthcare payer perspective.